Helping patients to improve self management of diabetes. (14th May 2004) - Cradock, S
Abstract : Research suggests that people with diabetes are poorly compliant with dietary and exercise recommendations, and that primary non-compliance with medication is common. Local research has shown that patients' beliefs about diabetes suggest little understanding of the seriousness of the disease in terms of increased mortality. Portsmouth Primary Care Trust, in collaboration with Portsmouth Hospitals NHS Trust, is developing a range of structured self management programmes to assist in helping people be clearer about how they can make changes that will reduce their risk of diabetes complications and cardiovascular disease. These programmes are delivered to groups of patients, rather than on a single patient basis.